Cultural Awareness and Translation Teaching On Junior High School at Cinta Budaya (Chong Wen) School - Marpaung, Muhammad Fauzi Romadhon; Ramadhanan, Raden Sri Ayu; Rambe, Shopiah Anggraini; Hariyanto, Hariyanto (Lembaga Riset Ilmiah, 2025)
The aims of the the study is to find out the significant between cultural awareness and translation teaching on Junior High School at Cinta Budaya (Chong Wen) and to know how cultural awareness and translation teaching on Junior High School at Cinta Budaya (Chong Wen) school. This research was conducted by qualitative research and the strategies and techniques on integrating culture into translation teaching on Junior High School are given for translation teaching by laying stress on imparting culture knowledge as well as translation skills so as to reduce students’ translation errors. The subjects of this study are 35 students in Class IX-B. The analysis on the investigation shows that the students are lack of cultural awareness and cultural knowledge, but they think culture knowledge is very important in avoiding translation errors in translation practice. In order to improve student’s cultural awareness and cultural knowledge, the following methods can be used in teaching translation.